Exploring the Feasibility of a Special Electoral Court to Achieve Electoral Justice - Septi Nur Wijayanti; Putri Anggia; Kelik Iswandi; Aulia Khansa Nabila (Universitas Negeri Semarang, 2026)
The increasing complexity and quantity of election disputes require a fairer, more transparent, independent, and quality settlement mechanism. Many Indonesian experts expressed support for the establishment of an electoral court because the existing dispute resolution mechanism lacked a sense of justice. Therefore, this study aims to address these problems through normative legal analysis using statutory and conceptual methods. To obtain comparative perspectives and relevant institutional models for the Indonesian context, we conducted a comparative study of electoral court practices in several Latin American countries. The results show that the debate surrounding the establishment of a special electoral court is seen as an initiative to promote fairness in resolving disputes. The Election Court provides legal certainty for justice seekers and eliminates the multi-institutional settlement of violations and conflicts. This is a strategic step to integrate dispute resolution that has been spread across various institutions (General Election Supervisory Agency, General Election Organizer Honorary Council, and Constitutional Court). The potential for this integration lies in enhancing the credibility of election results and minimizing authority overlap. This article offers integrative design ideas in resolving election disputes. This will ensure that substantial electoral justice is achieved, rather than just procedural justice. Thus, the Election Court is not only a new judicial instrument but also a representation of paradigm transformation in realizing substantial electoral justice in Indonesia.